A Mini-Review: Recent Advances in Coumarin-Metal Complexes With Biological Properties - Balewski, Łukasz; Szulta, Sylwia; Jalińska, Aleksandra; Kornicka, Anita (Frontiers in Chemistry, 2021)
The coumarin nucleus is a recurring motif in both natural and synthetic compounds that exhibit a broad spectrum of biological properties including anticoagulant, anti-inflammatory, antioxidant, antiviral, antimicrobial and anticancer agents as well as enzyme inhibitors. On the other hand, it has been reported that the incorporation of a metal ion into coumarin derivatives can increase the activity of such complexes compared to coumarin-based ligands. Accordingly, some of them have been found to display promising antioxidant, antitumor or antibacterial activities. This mini-review briefly summarizes the recent development of coumarin-metal complexes with proven biological properties. The attention is also paid to agents for which practical applications in the detection of biologically important species may be found.